A Modified Social Force Model For Crowd Dynamics - Thinakaran, Kumatha (2011)
The Social Force Model (SFM) is the most recent form of pedestrian model which is widely used in computer simulation software, as this model is more realistic. Many modifications have been done to improvise the SFM. One of them is a self-stopping mechanism introduced by earlier researchers where a respect factor is used to determine the self-stopping mechanism. The respect factor determines the respect area which is the area for pedestrians to walk at their own preferred speed. In this thesis, the constant respect factor is modified to obtain a better fundamental diagram.